ANALYZING THE PERCEPTION OF THE BLIND AND VISUALLY-IMPAIRED ON THE USE OF AUDIO DESCRIPTION: A CASE STUDY - Setiawan, Patricia Nanda; Halim, Suwarni Wijaya (Fakultas Ilmu Budaya, Universitas Mulawarman, 2026)
Disabled people, including the blind and visually impaired, need some accessibilities to help them doing some activities in their life. One of the assistance designed to help the blind and visually impaired is audio description. Audio description is a form of audiovisual translation which can be beneficial for the blind and visually impaired in accessing audiovisual works. However, audio description has not been applied widely in Indonesia. This research aims to investigate the perception of blind and visually impaired students in Mardi Wuto English Club on the use of audio description. The researchers interviewed eight blind and visually impaired students in Mardi Wuto English Club after they watched a short film without and with audio description on YouTube entitled “The Rose” produced by CHILDLINEIndia. The result indicated that the participants had a positive perception on the audio description as they found it helpful to comprehend the silent scenes and storyline in that short film.